Curative Effect and Mechanism of Guiren Runchang Granules on Morphine-Induced Slow Transit Constipation in Mice. (23rd September 2020) - Sun, Yihan; Yan, Chengqiu; Jin, Shifeng; Shi, Chong; Zhao, Jingming; Li, Guofeng
Abstract : Recent studies have identified the curative effects of traditional Chinese medicine for constipation. The mechanism of action of Guiren Runchang granules (GRGs) in the treatment of slow transit constipation (STC) was evaluated in this study. Here, we assessed the efficacy of GRG by comparing the differences in fecal characteristics, stool weight, and intestinal transit rate (ITR) among 6 groups ( n  = 12/group), which were administered three concentrations of GRG, mosapride, and saline. The influence of GRG on the SCF/c-kit pathway, AQP4, and serum motilin of mice was assessed through ELISA, western blot, and immunohistochemical analysis. The dry weight of mouse feces at 24 hr and ITR in the MD (medium-dose GRG; 9.44 g/kg/d) and HD (high-dose GRG; 18.88 g/kg/d) groups was higher than that in the MC (model control) group. The serum motilin of morphine-induced mice level was lower in the MC group than in the NC (normal control) group, and this condition was improved in the HD group. The HD group expressed significantly higher levels of SCF and c-kit protein but lower levels of AQP4 and simultaneously presented more SCF-positive and c-kit-positive cells. However, no differences in the serum SCF level were found among the six groups. Certain concentrations of GRG are effective in STC mice, the potential mechanism of which may be associated with repairing the SCF/c-kit pathway and reducing the expression of AQP4 in the colon. GRG improved the serum motilin level but had no influence on the serum SCF level.